2010
DOI: 10.1097/jto.0b013e3181d0a4f5
|View full text |Cite
|
Sign up to set email alerts
|

Primary Tumor Standardized Uptake Value Measured on Fluorodeoxyglucose Positron Emission Tomography Is of Prognostic Value for Survival in Non-small Cell Lung Cancer: Update of a Systematic Review and Meta-Analysis by the European Lung Cancer Working Party for the International Association for the Study of Lung Cancer Staging Project

Abstract: We confirmed the results of our previous review showing that SUV is potentially a very interesting factor for predicting patient outcome. We believe that a meta-analysis based on individual patient data would be of great value as allowing to assess the independent prognostic value, to take into account some factors responsible for heterogeneity between studies (SUV assessment method, disease stage, and histology), and to update survival data. We are planning to conduct such a meta-analysis on behalf of the Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
150
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(159 citation statements)
references
References 38 publications
5
150
1
3
Order By: Relevance
“…6) Our results show that FDG uptake measured by SUVmax is a prognostic factor in stage I lung adenocarcinoma treated with surgery, which is consistent with the results of previous studies. However, the definitions and implications of high-and low-risk PET findings have yet to be determined.…”
Section: Discussionsupporting
confidence: 93%
“…6) Our results show that FDG uptake measured by SUVmax is a prognostic factor in stage I lung adenocarcinoma treated with surgery, which is consistent with the results of previous studies. However, the definitions and implications of high-and low-risk PET findings have yet to be determined.…”
Section: Discussionsupporting
confidence: 93%
“…These cells must metabolize glucose by glycolysis, rather than oxidative phosphorylation, to prevent apoptosis, thereby increasing their glucose utilization. In turn, high levels of glucose metabolism, as inferred from 18 F-FDG PET studies, have been shown to correlate with poor outcome in patients with NSCLC (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…PET with 18 F-FDG, a radiolabeled form of glucose, exploits genomic and gene alterations in malignant cells that results in alterations in glucose metabolism, an effect first described by Otto Warburg in 1924 (4). There is evidence that alterations in glucose metabolism in primary lung tumors, resulting in greater glucose utilization and hence 18 F-FDG uptake, may correlate with a more aggressive phenotype (5,6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pour la 7 e édition, les facteurs pronostiques avaient été étudiés sur la banque de données de l'IASLC. Il y avait été proposé certains facteurs résumés dans le tableau 4, qui ont un rôle pronostique important, à savoir le stade clinique, l'indice de performance, l'âge, le sexe, et, dans certains cas, le type histologique, le SUVmax à la TEP et certains paramètres biologiques [23,24]. Tout ceci devrait être revu avec des données prospectives beaucoup plus complètes qui devraient être disponibles pour la classi cation suivante.…”
Section: Pronosticunclassified